Non-tuberculous mycobacterial disease associated with Mycobacterium montefiorense in salamanders - Komine, Takeshi; Ihara, Hyogo; Inohana, Mari; Kwok, Jennifer Caroline; Shimizu, Akane; Terasawa, Tsumugi; Miyazaki, Ayaka; Srivorakul, Saralee; Iwao, Hajime; Harada, Sachiko; Yoshida, Mitsunori; Hoshino, Yoshihiko; et al. (Frontiers in veterinary science, 2023)
Mycobacterium montefiorense is one of the causes of non-tuberculous mycobacterial infections in moray eels and salamanders. Although M. montefiorense infection could be a threat to salamanders, little information is available regarding this pathogen and associated infection. This study aimed to provide fundamental information regarding M. montefiorense and its infection in salamanders.IntroductionMycobacterium montefiorense is one of the causes of non-tuberculous mycobacterial infections in moray eels and salamanders. Although M. montefiorense infection could be a threat to salamanders, little information is available regarding this pathogen and associated infection. This study aimed to provide fundamental information regarding M. montefiorense and its infection in salamanders.Nine M. montefiorense strains isolated from three species of salamanders, namely, Japanese black salamander (Hynobius nigrescens), Hakuba salamander (H. hidamontanus), and Tohoku hynobiid salamander (H. lichenatus), between 2010 and 2018, were characterized based on phenotypic and genetic examination. We also pathologically observed salamanders infected with the M. montefiorense strains, including Hakuba salamanders and Tohoku hynobiid salamanders.MethodsNine M. montefiorense strains isolated from three species of salamanders, namely, Japanese black salamander (Hynobius nigrescens), Hakuba salamander (H. hidamontanus), and Tohoku hynobiid salamander (H. lichenatus), between 2010 and 2018, were characterized based on phenotypic and genetic examination. We also pathologically observed salamanders infected with the M. montefiorense strains, including Hakuba salamanders and Tohoku hynobiid salamanders.The microbiological and chemical characteristics of the M. montefiorense salamander and an eel strain (reference strain) matched. Susceptibility testing for antimicrobials suggested that clarithromycin may be effective. Regarding disinfectants, phtharal, peracetic acid, glutaral, sodium hypochlorite, and benzalkonium chloride may be effective. Phylogenetic analyses revealed that the strains isolated from salamanders in 2014 and 2018 were genetically closely related, which could indicate an outbreak. The main gross findings in infected salamanders include skin ulcerative lesions or nodules in the enlarged liver. Microscopically, multifocal to coalescent granulomatous lesions composed of massive macrophages containing numerous acid-fast bacilli were prominently observed in the liver.ResultsThe microbiological and chemical characteristics of the M. montefiorense salamander and an eel strain (reference strain) matched. Susceptibility testing for antimicrobials suggested that clarithromycin may be effective. Regarding disinfectants, phtharal, peracetic acid, glutaral, sodium hypochlorite, and benzalkonium chloride may be effective. Phylogenetic analyses revealed that the strains isolated from salamanders in 2014 and 2018 were genetically closely related, which could indicate an outbreak. The main gross findings in infected salamanders include skin ulcerative lesions or nodules in the enlarged liver. Microscopically, multifocal to coalescent granulomatous lesions composed of massive macrophages containing numerous acid-fast bacilli were prominently observed in the liver.This study contributes to our understanding of the genetic diversity and phenotypic characteristics of M. montefiorense, as well as the pathology of the infection.ConclusionThis study contributes to our understanding of the genetic diversity and phenotypic characteristics of M. montefiorense, as well as the pathology of the infection.